The Mediterranean sea : temporal variability and spatial patterns - Borzelli, Gianluca Eusebi; Gacic, Miroslav; Lionello, Piero (Hoboken, NJ : American Geophysical Union/WILEY, 2014)
'Surface, intermediate and deep water processes and their interaction in time and space drive the major ocean circulation of the Mediterranean Sea. The Mediterranean Sea is a comprehensive volume that investigates the temporal and spatial variability patterns in the ocean basin. All major forcing mechanisms, such as surface wind forcing, buoyancy fluxes, lateral mass exchange and deep convection determining the global oceanic circulation are present in the Mediterranean Sea. Deep and intermediate water masses are formed in different areas of the ocean layers and they drive the Mediterranean thermohaline cell, which further shows important analogies with the global ocean conveyor belt. Volume highlights include discussions of the following: Represents state-of-the-art physical and biogeochemical properties of the Mediterranean Sea Investigates multiple physical ocean circulation processes, both in time and spatial scales (basin, sub-basin and mesoscale) Different regional phenomena in the sea influence the biogeochemistry of the basin and the ocean dynamics Examines spatio-temporal variability of the surface circulation in the Western Mediterranean Examines deep-water variability and inter-basin interactions in the Eastern Mediterranean Sea Portrays a strong understanding the global ocean circulation patterns and the global climate The Mediterranean Sea will be a valuable resource for geoscientists, oceanographers and meteorologists.'--
'Represents state-of-the-art physical and biogeochemical properties of the Mediterranean Sea'--
Includes bibliographical references and index.
Keywords: Chemical oceanography; Biogeochemical cycles; Ocean circulation; Ocean currents; Mediterranean Sea